Modelling of PDC drill bit whirling - Prigorovska, Tania O. (My University, 2007)
At this work it was made the attempt to explain the process of PDC drill bit whirling as an integral part of drilling in real conditions. It was shown that the causes of PDC whirling are not only the rock mass heterogeneity, but drill bit mass misbalance too and it is impossible to obtain absolutely stable drilling system. PDC drill bit previous models were based on the assumption all cutting forces are stable and that PDC drill bit oscillation is self appearable or stochastic. Based on the theory of probability it was defined the value of cutting forces on every PDC cutter and generalized drill face reaction and it was drill bit oscillation and whirling were analyzed.

W artykule podjęto próbę wyjaśnienia procesu wirowania świdra PDC jako integralnej części rzeczywistych warunków wiercenia. Wykazano, że przyczyną powstawania ruchu wirowego jest nie tylko niejednorodność górotworu, ale również brak wyważenia świdra i ogólna niemożność stworzenia całkowicie stabilnego układu wiertniczego. Poprzednie modele świdra były oparte na założeniu, że wszystkie siły tnące są stabilne i że oscylacje świdra same się pojawiają lub są stochastyczne. Opierając się na teorii prawdopodobieństwa, określono wartość sił tnących dla każdego ostrza i uogólniono reakcję czoła świdra. Następnie przeanalizowano oscylacje świdra i zjawiska wirowania.
Modelowanie wirowego ruchu świdra PDC
Wiertnictwo, Nafta, Gaz
Keywords: drillstring; oscillations; PDC bit; przewód wiertniczy; whirling; oscylacje; świder PDC; kinetic energy; wirowanie; energia kinentyczna; rock mass; górotwór